TECHNOLOGY ADOPTION AND COOPERATIVE MANAGEMENT: A CASE STUDY IN FAMILY FARMING - Cribb, André Yves; Cribb, Sandra Lucia de Souza Pinto; Junior, Murillo Freire; Silva, Fernando Teixeira (Science & Technology Journals, 2011)
The technical literature on agricultural business management recognizes that the cooperativism and the technology are relevant factors to the survival and competitiveness of family farming. This article aims to study the interactions between those two factors and their impact on the management of systems of family agricultural production, taking as a reference the chain of the coconut of the Northern Region of the State of Rio de Janeiro. It is part of the scope of a research carried out at the Mixed Cooperative of Rural Producers of Quissamã (COOPQ). The methodological procedures - used in the collection, analysis and interpretation of data and information - fit in what is called rapid rural appraisal (RRA), which is focused on case study. The results of the research show that technological adoption and significantly influence each other and that their interactions cause not only economic impacts but also social and environmental impacts. By examining these two factors, this article provides subsidies not only for studies and practices of business management, but also for the definition and reformulation of public policies in the context of family farming.